2020
DOI: 10.1108/jfra-01-2019-0007
|View full text |Cite
|
Sign up to set email alerts
|

IFRS adoption, corporate governance and management earnings forecasts

Abstract: Purpose This paper aims to examine whether International Financial Reporting Standards (IFRS) adoption and corporate governance attributes increase the management earnings forecasts’ accuracy disclosed in prospectuses for French Initial Public Offerings (IPOs). Design/methodology/approach The analysis is based on cross-sectional regression explaining the absolute forecast errors by using 45 French firms that made IPOs between 2005 and 2016 in two French financial markets: Euronext and Alternext. Findings I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 62 publications
1
9
0
Order By: Relevance
“…For this purpose, the company is required to improve its information context through the publication of quality forecasts (Labégorre and Boubaker, 2005). In agreement with the agency theory and the signaling theory, Hlel et al (2020) find that the IFRS adoption and effective corporate governance, proxied by the board characteristics, increase the accuracy of management forecasts.…”
Section: Literature Review and Hypotheses Developmentsupporting
confidence: 77%
“…For this purpose, the company is required to improve its information context through the publication of quality forecasts (Labégorre and Boubaker, 2005). In agreement with the agency theory and the signaling theory, Hlel et al (2020) find that the IFRS adoption and effective corporate governance, proxied by the board characteristics, increase the accuracy of management forecasts.…”
Section: Literature Review and Hypotheses Developmentsupporting
confidence: 77%
“…As asserted in agency theory, corporate governance is an important mechanism to prevent opportunistic management behaviour (Hlel et al , 2020). Corporate governance is a series of supervisory mechanisms that protect investors’ interests (La Porta et al , 2000; Utama et al , 2017).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Despite the value relevance of analysts’ forecasts, prior research has also shown that stock price reactions to earnings announcements are stronger than the response to analysts’ forecast revisions (Bartov et al , 2002; Esterer and Schröder, 2014). Consistent with the notion that earnings figures are important to investors (Ammer and Ahmad-Zaluki, 2017; Hlel et al , 2019), recent research shows that firms actively manage their earnings (or analysts’ expectations) to MBE forecast consensus (Bartov et al , 2002; Kim and Song, 2015; Masumoto, 2002; Zhang et al , 2018). According to Huang et al (2017), when the firm’s reported quarterly earnings equals the most recent consensus analyst forecast for that quarter or exceeds it by a cent, the firm is considered as having “met” its analyst earnings forecast.…”
Section: Introductionmentioning
confidence: 69%
“…As suggested by Chang et al (2016) and Schipper (1991), prior studies failed to consider the full decision context and economic incentives that affect analysts’ forecasts. Although analysts’ decision context is an area where research is relatively lacking, there are some follow on studies that suggest that analysts are motivated to make more accurate forecasts (Ahmed et al , 2020; Hlel et al , 2019; Mikhail et al , 1999; Rahman et al , 2019; Wang et al , 2017). Consistent with the view that analysts’ objective is to make more accurate forecasts, Hong et al (2020) and Previts and Bricker (1994) observed that analysts prefer following financial institutes with effective earnings management.…”
Section: Literature Reviewmentioning
confidence: 99%